A Spray Foliar Containing Methylobacterium symbioticum Did Not Increase Nitrogen Concentration in Leaves or Olive Yield Across Three Rainfed Olive Orchards - Manuel Ângelo Rodrigues; João Ilídio Lopes; Sandra Martins; Cátia Brito; Carlos Manuel Correia; Margarida Arrobas (Horticulturae)
Biological nitrogen (N) fixation has been advocated in agricultural fields due to being considered a more sustainable way to introduce N into agrosystems than industrial N fertilizers. In this study, a foliar spray inoculant containing the microorganism Methylobacterium symbioticum was applied. This microorganism is known for fixing N in the phyllosphere, regardless of the cultivated species. This study was conducted in three rainfed olive orchards over three years. In two orchards managed according to European Union (EU) integrated production rules, the experiment was organized as a factorial design with inoculant (applied at two levels, yes and no) and N fertilization (applied to the soil at three levels, 0, 40, and 80 kg ha−1 of N). The third trial, managed according to EU organic farming rules, was organized in a completely randomized design with three treatments: with (yes) and without (no) inoculant and with a treatment involving a seaweed extract, also for foliar application. The microbiological inoculant did not consistently influence olive yield or N concentration in leaves across the three trials. Conversely, N application to the soil significantly influenced N concentration in leaves and olive yield. In one of the trials, in the third year of the study, soil N application (80 kg ha−1) resulted in an olive yield of ~eight times higher than the unfertilized control treatment. The seaweed extract also did not lead to significant differences in leaf mineral composition or olive yield compared with the other treatments. These findings from the on-farm research highlight the importance of accurately determining the conditions under which commercial products can deliver effective results. It is crucial to acknowledge that these products involve expenses not only in their acquisition but also in their application.